Contract Damages, Moral Agency, and Henry James' The Ambassadors. Issue 2 (August 2019) - Nadler, Jennifer
Abstract: This paper enters the dispute over the proper interpretation of the expectation measure of damages in contract law. Should damages be measured by the plaintiff's financial loss or by the cost of acquiring a substitute performance ("cost of cure")? I begin by presenting a moral (as opposed to an economic or a pragmatic) justification for the traditional contract principle that a plaintiff has a right to compensation for the financial loss flowing from breach but no right to performance. I do so by showing that implicit in the principle that the plaintiff has a right to compensation for financial loss alone is a conception of moral agency as a capacity for detachment from things. Through an exploration of Henry James' novel The Ambassadors, I try to show what is valuable in that conception, although I argue that it is, in the end, incomplete. Then I consider the self-authorship conception of moral agency implicit in the moralist's proposal to replace the financial loss remedy with a right to performance or to compensation for the cost of securing a substitute performance. Again, through a reading of James' novel, I try to show what is valuable in this conception although I argue that it too is incomplete. I suggest that the conceptions of moral agency respectively implicit in the financial loss and cost of cure remedies are constituent parts of a complete conception. Once we see this, we arrive at a moral justification for a contract law which treats compensation for financial loss as the normal rule but exceptionally allows for a remedy that aims at securing performance.